Weak hybridization and isolated localized magnetic moments in the compounds CeT2Cd20 (T = Ni, Pd). (20th July 2015) - White, B D; Yazici, D; Ho, P-C; Kanchanavatee, N; Pouse, N; Fang, Y; Breindel, A J; Friedman, A J; Maple, M B
Abstract: We report the physical properties of single crystals of the compounds CeT2 Cd20 (T = Ni, Pd) that were grown in a molten Cd flux. Large separations of ∼6.7–6.8 Å between Ce ions favor the localized magnetic moments that are observed in measurements of the magnetization. The strength of the Ruderman–Kittel–Kasuya–Yosida magnetic exchange interaction between the localized moments is severely limited by the large Ce–Ce separations and by weak hybridization between localized Ce 4 f and itinerant electron states. Measurements of electrical resistivity performed down to 0.138 K were unable to observe evidence for the emergence of magnetic order; however, magnetically-ordered ground states with very low transition temperatures are still expected in these compounds despite the isolated nature of the localized magnetic moments. Such a fragile magnetic order could be highly susceptible to tuning via applied pressure, but evidence for the emergence of magnetic order has not been observed so far in our measurements up to 2.5 GPa.